In Vivo Expression of Recombinant Pregnancy-Specific Glycoprotein 1a Inhibits the Symptoms of Collagen-Induced Arthritis - Falcón, Cristian Roberto (2014)
Problem The contribution of Pregnancy-specific glycoproteins (PSG), the major variant of PSG released into the circulation during pregnancy, to the pregnancy-dependent improvement of rheumatoid arthritis (RA) has still not been elucidated. Method of study Collagen-induced arthritis (CIA) was used to test the hypothesis that PSG1a when released into circulation has a modulatory role on the Th1-pathogenic response, thus improving the CIA symptoms. In vivo expression of PSG1a was induced by injection of the vaccinia (Vac)-based expression vector harboring the complete open-reading frame of PSG1a cDNA. Results In vivo PSG1a expression during the induction of CIA ameliorated the clinical symptoms, thereby reducing the arthritis score and incidence. Significantly lower levels of IL-17, IL-6, and IFN-γ, but higher levels of TGF-β and IL-10 were secreted by collagen type II-stimulated spleen mononuclear cells from Vac-PSG1a-treated mice compared with control mice. Moreover, Vac-PSG1a treatment promoted the increase in splenic CD4+CD25+Foxp3+ Treg cells. Conclusion Pre-clinical Vac-PSG1a treatment suppressed the Th1- and Th17-type-specific responses, leading to an increase in splenic Treg cells as well as IL-10- and TGF-β-secreting cells, with the CIA symptoms being ameliorated.